2020
DOI: 10.1021/acsami.9b20902
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-Induced Exfoliation Provides Onion-Like Graphene-Surrounded MoS2 Nanosheets for a Highly Efficient Hydrogen Evolution Reaction

Abstract: With the goal of obtaining sustainable earth-abundant electrocatalyst materials displaying high performance in the hydrogen evolution reaction (HER), here we propose a facile one-pot plasmainduced electrochemical process for the fabrication of new core−shell structures of ultrathin MoS 2 nanosheets engulfed within onion-like graphene nanosheets (OGNs@MoS 2 ). The resultant OGNs@MoS 2 structures not only increased the number of active sites of the semiconducting MoS 2 nanosheets but also enhanced their conducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(25 citation statements)
references
References 56 publications
2
23
0
Order By: Relevance
“…Notably, the presence of rGO and MoS 2 contributed significantly to the absorption of visible light and effectively limited the recombination of electron–hole pairs, which extended lifetime of the photogenerated electrons and made more electrons participate in the evolution of H 2 . We concluded that MoS 2 /rGO appeared to be a key factor to enhance photocatalytic performance 60 . Thus, these kinds of structural CdS/MoS 2 /rGO nanocomposites could achieve high H 2 evolution rates and played an important role in improving the activity for HER.…”
Section: Resultsmentioning
confidence: 91%
“…Notably, the presence of rGO and MoS 2 contributed significantly to the absorption of visible light and effectively limited the recombination of electron–hole pairs, which extended lifetime of the photogenerated electrons and made more electrons participate in the evolution of H 2 . We concluded that MoS 2 /rGO appeared to be a key factor to enhance photocatalytic performance 60 . Thus, these kinds of structural CdS/MoS 2 /rGO nanocomposites could achieve high H 2 evolution rates and played an important role in improving the activity for HER.…”
Section: Resultsmentioning
confidence: 91%
“…[28,29] Nguyen et al synthesized the MoS 2 nanosheets covered by onion-like graphene nanosheets (OGNs@MoS 2 ) through a facile one-pot plasma-induced method. [30] OGNs@MoS 2 not only exposed the active sites to a greater degree but also displayed the enhanced conductivity. Sun et al reported MoS 2 nanosheets with edge-oriented geometry grown on rGO, which could effectively expose more catalytical active MoS 2 edges.…”
Section: Introductionmentioning
confidence: 99%
“…A great number of efforts have been devoted to enhance its HER performance, including phase and structure control, [23–25] surface modification, [26,27] doping, and/or stoichiometric changes [28,29] . Nguyen et al synthesized the MoS 2 nanosheets covered by onion‐like graphene nanosheets (OGNs@MoS 2 ) through a facile one‐pot plasma‐induced method [30] . OGNs@MoS 2 not only exposed the active sites to a greater degree but also displayed the enhanced conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…15 Based on various types of synthesis to obtain thin layers of graphene, 16,17 cathodic plasma is one of the best ways to synthesize thin layer graphene nanosheets with high purity, and large volume in a short time. [17][18][19] Based on that, in this study an improved cathodic plasma method is introduced, which can be used to obtain graphene nanosheets with a higher purity.…”
Section: Introductionmentioning
confidence: 99%